The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/d14010050
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Video as a Tool to Quantify Fish Density in Complex Coastal Habitats

Abstract: Habitat loss is a serious issue threatening biodiversity across the planet, including coastal habitats that support important fish populations. Many coastal areas have been extensively modified by the construction of infrastructure such as ports, seawalls, docks, and armored shorelines. In addition, habitat restoration and enhancement projects often include constructed breakwaters or reefs. Such infrastructure may have incidental or intended habitat values for fish, yet their physical complexity makes quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The metrics of MaxN T and species richness had an even lower ratio of 0.5:1, as the entire video can be watched at 2× speed for RUV data in these low abundance habitats. A recent study on RUVs suggested using Frequency of Occurrence, a presence/absence metric derived from species richness, in situations where a quick and robust assessment of fish assemblage composition is required ( Baker et al, 2022 ). Researchers could consider this method over subsampling when fast data processing is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metrics of MaxN T and species richness had an even lower ratio of 0.5:1, as the entire video can be watched at 2× speed for RUV data in these low abundance habitats. A recent study on RUVs suggested using Frequency of Occurrence, a presence/absence metric derived from species richness, in situations where a quick and robust assessment of fish assemblage composition is required ( Baker et al, 2022 ). Researchers could consider this method over subsampling when fast data processing is required.…”
Section: Discussionmentioning
confidence: 99%
“…Other field and simulation studies have shown that it can be less precise than MaxN, and potentially over-inflate zero counts ( Stobart et al, 2015 ; Campbell et al, 2015 ). Their relative value can change based on useage, as for RUVs in complex habitats there is high correlation between the two for structure-oriented species, but less so for mobile species ( Baker et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment presented by (28) cannot be used to detect the exact location and species of fish that the proposed model has performed. The model built by (10) could not detect the species, has reduced performance at a lower resolution, and cannot pinpoint the exact location of the fish. The presented model has addressed all of these parameters.…”
Section: Comparison With the State-of-the-artmentioning
confidence: 99%
“…The experiment presented by [73] cannot be used to detect the exact location and species of fish that the presented model has performed. The model built by [74] could not detect the species, has reduced performance at a lower resolution, and cannot pinpoint the exact location of the fish and all of these parameters have been addressed by the presented model. [75,81] had performance degradation at lower resolution images where the method proposed in the experiment had obtained higher accuracy, which is 96.5% for lower resolution as well.…”
Section: Comparison With the State-of-the-artmentioning
confidence: 99%